Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share Terhadap Peningkatan Kompetensi Belajar Ilmu Pengetahuan Alam: Implementation of Think Pair Share Cooperative Learning Model on the Improvement of Science Learning Competencies - Gusmiharti, Rina; Fitri, Rahmadhani (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to look at the effect of the cooperative learning model type Think Pair Share on the improvement of the students' learning competencies in the material in the class VIII Excretion System in SMP 6 . This research is an experimental study with a Randomized Control Group Only Design study design. Sampling is done by using sampling technique, which is selected class VIII 2 as the experimental class and class VIII 1 as the control class. The research instrument used was the question for knowledge competence, the observation sheet for attitude competence. The hypothesis in this study was tested using a t test which was first carried out a prerequisite test, namely the normality test and homogeneity test. Based on the t-test it is known that the competencies of knowledge and competence in the attitude of > t table are (2.56> 1.67) and (5.48> 1.67). This shows that the hypothesis is accepted. So it can be concluded that the application of the cooperative learning model type Think Pair Share can improve students' learning competencies in SMP 6.